2002
DOI: 10.4049/jimmunol.169.10.5919
|View full text |Cite
|
Sign up to set email alerts
|

Bax is Crucial for IFN-γ-Induced Resolution of Allergen- Induced Mucus Cell Metaplasia

Abstract: Allergic airway responses cause proliferation of epithelial cells and mucus cell metaplasia (MCM), and the resolution of MCM involves reduction of cell numbers. The role of inflammation and apoptosis on this process was investigated in P-selectin +/+ and −/− mice sensitized and challenged with OVA by analyzing the expression and the role of regulators of apoptosis in metaplastic mucus cells. No differences were observed in MCM at 5 days of allergen exposure between +/+ and −/− mice, despite reduced IL-13 level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 30 publications
1
34
1
Order By: Relevance
“…Our previous findings showed that Bax is important for the resolution of MCH during prolonged exposure to allergen (11). However, Bax mRNA and protein levels were not increased in IFN-␥-treated human and murine AECs and our cell fractionation studies with human AECs did not detect any noticeable movement of Bax from the cytosol to the mitochondria in response to IFN-␥.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Our previous findings showed that Bax is important for the resolution of MCH during prolonged exposure to allergen (11). However, Bax mRNA and protein levels were not increased in IFN-␥-treated human and murine AECs and our cell fractionation studies with human AECs did not detect any noticeable movement of Bax from the cytosol to the mitochondria in response to IFN-␥.…”
Section: Discussioncontrasting
confidence: 56%
“…These events lead to mitochondrial membrane permeabilization (8), or calcium release from the endoplasmic reticulum (ER) (9,10) to initiate activation of caspases and DNases and the appearance of apoptotic morphology. The resolution of allergen-induced MCH by IFN-␥ is not mediated by the death signal Fas (4), but we have shown that Bax knockout (bax Ϫ/Ϫ ) mice exhibit delayed resolution of MCH compared with their wild-type littermates, suggesting that Bax is involved in the resolution of allergen-induced MCH (11). However, the path linking IFN-␥ and STAT1 to cellular apoptosis in hyperplastic mucous cells is unclear.…”
Section: P Ersistent Mucous Cell Hyperplasia (Mch)mentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue sections were stained with Alcian blue (AB) and periodic acid Schiff or hematoxylin and eosin as described previously (20). The number of AB-positive cells per millimeter of basal lamina and per total cell count were quantified using a light microscope (BH-2; Olympus, Melville, NY) equipped with the Image analysis system (National Institutes of Health) as described previously (26).…”
Section: Mice and Adenoviral Infectionmentioning
confidence: 99%
“…The cell death of airway epithelial cells (AECs) during the resolution of metaplastic mucous cells is regulated by the Bcl-2 family of proteins (20,21), and involves the intrinsic apoptotic pathway (22). During the resolution of allergen-induced epithelial and mucous cell hyperplasia that is mediated by IFN-g, we showed that STAT1 and Bik, a proapoptotic Bcl-2 family member, are crucial factors, because unlike wild-type mice, STAT1-and Bik-deficient mice fail to resolve mucous cell metaplasia (MCM).…”
mentioning
confidence: 99%